Effectiveness of a gamified educational application on attention and academic performance in children with ADHD: an 8-week randomized controlled trial - Dai, JiaMin; Wufue, Ailifeire; Zhang, Hong (Frontiers in Education, 2025)
IntroductionGamified educational interventions are promising tools to improve attention and academic outcomes in children with attention-deficit/hyperactivity disorder (ADHD), but evidence from randomized controlled trials (RCTs) and data on long-term maintenance remain limited. We evaluated a specifically designed gamified educational application against a non-gamified digital program matched for content and duration.MethodsEighty children aged 6–12 years with clinically diagnosed ADHD were randomly assigned to a gamified intervention group (n = 40) or a control group (n = 40). Both groups completed identical learning tasks (calculation, text comprehension, phonological exercises) over 8 weeks; only the intervention group received gamification elements (immediate feedback, rewards, level-based challenges). Baseline and post-intervention assessments included visual and auditory reaction time tests, a continuous performance test, and standardized academic tests in reading, writing, and mathematics. A follow-up assessment was scheduled 8 weeks after training.ResultsAfter 8 weeks, the gamified group showed greater improvements than the control group in visual and auditory reaction times and sustained attention (all p < 0.01), as well as in reading, writing, and mathematics scores. Training time was comparable between groups.DiscussionAn 8-week gamified educational intervention significantly enhanced attention and academic performance in children with ADHD compared with a non-gamified program, suggesting that well-designed gamified applications may serve as engaging, accessible tools to support cognitive and educational outcomes.